Shielding implications on secondary radiation doses in prostate cancer treatment. (September 2020) - Medeiros, Marcos P.C.; Silva, Ademir X.; Rebello, Wilson F.; Santos, Raphael F.G.; Stenders, Ricardo M.; Braz, Delson; Braga, Kelmo L.; Thalhofer, Jardel L.; Berdeguez, Mirta B.T.; Andrade, Edson R.
Abstract : Abstract: Medical linear accelerators (linacs) require a physical structure designed to provide adequate structural support which ensures the safety of patients, operators and the general public. During a radiotherapy session, healthy tissues are exposed to radiation, even with these safety guarantees. This unwanted exposure may increase the likelihood of developing secondary cancer. This work uses the MCNP-5 code to computationally simulate a conformational 3D radiotherapy protocol for prostate cancer. Also, it investigates the potential effects of radiotherapy room shielding composition on equivalent and effective doses in the patient's body. A computational model of an actual room was developed considering a Varian Trilogy linac operating at 10 MeV. This model enabled dose calculations for an anthropomorphic phantom called REX to be performed. This phantom has sufficient details of all relevant organs and tissues needed to estimate the effective dose of the patient. The treatment protocol modeled in this study came from the database of patients treated by the Brazilian National Cancer Institute (Inca). For this protocol, the total dose to be applied to the patient is equally distributed over the four gantry inclination angles (0°, 90°, 180° and 270°). The simulated results suggested that the equivalent dose on different organs and tissues has been increased by concrete shielding. Regarding the effective dose due to the presence of additional shielding (steel or lead), the simulation suggests that such variations can be considered small. Overall the results allowed quantifying the specific contribution of concrete, lead, and steel as part of shielding on the equivalent and effective doses in the patient. Highlights: The concrete shielding contributes to the increase of the patient's equivalent dose. The contribution of 1 TVL of steel or lead in the primary belt would be irrelevant. The dose portion attributed to shielding is approximately homogeneous outside the treatment region. The equivalent dose for several organs/tissues is impacted by lead/steel shielding.